AN EVALUATION OF THE PLACE OF MORALITY AND ETHICS IN ISLAMIC CIVIL LAW AND CONTEMPORARY TURKISH CIVIL LAW - Akturk, Hatice (Mimbar Hukum, 2024)
Abstract Like morality, law as a phenomenon develops in a process along with inevitable radical breaking points. Nevertheless, the phenomenon of law, which is constantly changing and developing, takes into many elements from past events, especially past legal systems. In this regard, the current Turkish law comes in handy as it departed during the Republican era from the Islamic legal system practiced for centuries and transitioned to the modern continental European legal system, nourished by many elements of Islamic law in the process. This article will examine the relationship between law, morality, and ethics by focusing on the similarities between these two legal systems. Abstrak Sama halnya dengan moralitas, hukum sebagai sebuah fenomena berkembang dalam sebuah proses yang disertai dengan titik-titik terobosan radikal yang tak terelakkan. Tak dapat dipungkiri bahwa fenomena hukum yang terus berubah dan berkembang mengambil banyak elemen dari peristiwa masa lalu, terutama sistem hukum masa lalu. Dalam hal ini, hukum Turki saat ini sangat berguna karena berasal pada era Republik dari sistem hukum Islam yang dipraktikkan selama berabad-abad dan yang bertransisi ke sistem hukum Eropa kontinental yang terpengaruhi berbagai elemen hukum Islam dalam prosesnya. Artikel ini akan membahas hubungan antara hukum, moralitas dan etika dengan berfokus pada kesamaan antara kedua sistem hukum ini.